DAMPAK KEGAGALAN REZIM KHADAFI TERHADAP MENINGKATNYA ESKALASI KONFLIK DAN INTERVENSI GLOBAL - Hardi Alunaza SD; Rachma Putri (Universitas Pendidikan Muhammadiyah Sorong, 2021)
This paper aims to explain how the influence of the Gaddafi regime's failure on the escalation of conflict and global intervention. The failure experienced by the Gaddafi regime resulted in a civil war in fighting over the Libyan region which was supported by acts of rebellion from various strongholds of community alliances. Through a qualitative approach, this paper will use the principle agent theory, peacekeeping, and domino theory as a conceptual framework in describing phenomena. Data sources in this paper were obtained from literature studies in the form of literature from journals, research reports, and reliable online news to support the analysis. The results of this study show that the continuation of the Libyan conflict escalation occurred after the rise of the Melati Revolution and the Arab Spring in Libya which led to the overthrow of the Gaddafi regime which actually resulted in the formation of a war between West Libya and East Libya along with the presence of the NTC, GNC and the global intervention of the United States / NATO, the United Nations take part inmitigating the conflict to date. The escalation of the conflict that occurred not only covered the seizure of the territory but also covered all aspects of Libyan people's lives that triggered chaos, rebellion, a feeling of injustice, fear and could cause the Libyan state to step down.